2019
DOI: 10.1111/jbi.13554
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Miocene dispersal events explain the cosmopolitan distribution of the Hypogymnioid lichens

Abstract: Aim Contemporary species’ distributions are shaped by both geography and historical events, such as extinction, diversification in specific areas and long‐distance dispersals. In the most diverse family of lichen‐forming fungi, Parmeliaceae, the Hypogymnioid clade, is an example of an evolutionary lineage comprised of species occurring in temperate to subpolar regions in both hemispheres. Here, we elucidate the timing of diversification events and the impact of historical events on the species distribution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…Based on current, limited sampling, we found a mix of a few cosmopolitan lineages and many local/regional endemics. Other lichen-forming fungi have shown similar patterns of complex intercontinental species distributions [ 82 , 83 , 84 , 85 ]. Presently, little is known of evolutionary processes that may give rise to reproductive isolation and ultimately speciation among populations in the L. polytropa clade.…”
Section: Discussionmentioning
confidence: 99%
“…Based on current, limited sampling, we found a mix of a few cosmopolitan lineages and many local/regional endemics. Other lichen-forming fungi have shown similar patterns of complex intercontinental species distributions [ 82 , 83 , 84 , 85 ]. Presently, little is known of evolutionary processes that may give rise to reproductive isolation and ultimately speciation among populations in the L. polytropa clade.…”
Section: Discussionmentioning
confidence: 99%
“…Our results allow us to hypothesize that long-distance dispersal might have played a crucial role in colonizing transcontinental regions. In lichenized fungi, wide distributional ranges have often been attributed to long-distance dispersal (Geml et al 2010;Amo de Paz et al 2012;Del-Prado et al 2013;Leavitt et al 2013Leavitt et al , 2018Núñez-Zapata et al 2017;Cubas et al 2018;Divakar et al 2019). Distinguished by an absence of soralia and isidia, a uniformly dark brown thallus, laminal and marginal pseudocyphellae, nonsquarrose rhizines, and by containing protocetraric and ±lobaric acids as characteristic substances (Thell et al 2011).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…A number of lichen species exhibit large distributional ranges, often being cosmopolitan, pantropical or antitropical (e.g., Galloway, 2008;Werth, 2011;Printzen et al, 2013;Leavitt and Lumbsch, 2016). However, molecular data have shown that many widely distributed species consist of separate lineages on different continents (Arguello et al, 2007;Otálora et al, 2010;Amo de Paz et al, 2012;Divakar et al, 2019). Species with worldwide distributional ranges usually are restricted to specific habitats -e.g., arctic species that occur in temperate regions are usually restricted to higher altitudes (Poelt, 1987).…”
Section: Discussionmentioning
confidence: 99%